Synoptic, redactional, stylistic and narratological observations on the retelling of Mark 7:30 in Matthew 15:28 - Smit, Peter-Ben A. (HTS teologiese studies, 2014)
The Matthean redaction of Mark 7:30 in Matthew 15:28 often receives scant attention in scholarship in terms of its narrative quality. At most, it is regarded as a truncation of the full Marcan version, while all attention is given to Matthew’s introduction of the notion of ‘faith’ in this verse. This article argues, by contrast, and on the basis of a synoptic comparison and narratological analysis of both texts, that more justice is done to both versions of the conclusion of this healing miracle when understanding them as achieving different narrative effects, with Matthew focusing on the immediacy of the healing, while Mark creates suspense, thus focusing on the veracity of Jesus’ statement that the girl in question is healed.